Contemporary African art : issues and perspectives in the globalized market - (:unkn) unknown (My University, 2013)
The contemporary African art has made its entry into the globalized system, first through artistic exhibitions then in the auction houses. Since the 1960s’ a new vision of contemporary African art has emerged with the postcolonial discourse. These ideas have led to a different reading of the contemporary African aesthetic with the support of some curators. Meanwhile, a vision of the “authentic” artist remains in many European and American exhibitions. African artist give an image that can sometimes seem fossilized The contemporary African artists today find themselves in a situation, which can be source of conflicts. They can get close to the artistic centers pulse which means the Western art market or stay on the African continent and try by different initiatives to include a market which is still outlying areas like western countriesThe other areas however gradually mutate into centers pulse but remain modest for the time being. With the advent of new technologies, opportunities exist for artists from the third world in terms of use but also as media. Their application pushes the reflection, and then attempt to understand the challenges that lies ahead for contemporary African art and perspectives that will glimpse through the paradigm of postcolonial studies and through the advent of technologies of information and communication. Is it possible to suggest new approaches to promote the dissemination of contemporary African art through socio-technical devices available but also through information management? The first part, this thesis attempts to show the diversity of the arts of Africa to understand it’s complexity today. Then by analyzing the relationship it has with the West, to understand it’s history.The second part tries to understand the identity of the African artist but also its positioning and initiatives that are carried out on the continent will better understand the challenges and opportunities.The third part will give a
Keywords: African Research